2011
DOI: 10.1097/ta.0b013e3181e3e5c1
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of l-Arginine in Experimental Acute Spinal Cord Injury Impairs Long-Term Motor Function Recovery

Abstract: L-arginine as used here interfered with the functional outcome of rats subjected to SCI, suggesting that L-arginine or its metabolic products may be neurotoxic. Because of its potential utility for acute SCI suggested in the past, strategies should be designed to block its apparent neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Some studies have shown that arginase is very important in providing ornithine as a precursor to the synthesis of polyamines, which are involved in the control of DNA, RNA, and protein synthesis during cell growth, differentiation, and development (Fozard et al, 1980;Pegg et al, 1982;Hougaard, 1992) and are important in embryonic development (Kusunoki and Yasumasu, 1978) . Some studies reported that hyperargininemic patients have as their primary symptoms delayed development associated with progressive spastic paraparesis (Scaglia and Lee, 2006;Esquivel-Aguilar et al, 2011). The Arg doses chosen in this study are consistent with those levels achieved in plasma and cerebrum of hyperarginemic patients which ranges around of 1.3 mM and 0.3 nmol/kg, respectively (Buchmann et al, 1996).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some studies have shown that arginase is very important in providing ornithine as a precursor to the synthesis of polyamines, which are involved in the control of DNA, RNA, and protein synthesis during cell growth, differentiation, and development (Fozard et al, 1980;Pegg et al, 1982;Hougaard, 1992) and are important in embryonic development (Kusunoki and Yasumasu, 1978) . Some studies reported that hyperargininemic patients have as their primary symptoms delayed development associated with progressive spastic paraparesis (Scaglia and Lee, 2006;Esquivel-Aguilar et al, 2011). The Arg doses chosen in this study are consistent with those levels achieved in plasma and cerebrum of hyperarginemic patients which ranges around of 1.3 mM and 0.3 nmol/kg, respectively (Buchmann et al, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…Some studies reported that hyperargininemic patients have as their primary symptoms delayed development associated with progressive spastic paraparesis (Scaglia and Lee, 2006; Esquivel‐Aguilar et al, 2011). The Arg doses chosen in this study are consistent with those levels achieved in plasma and cerebrum of hyperarginemic patients which ranges around of 1.3 mM and 0.3 nmol/kg, respectively (Buchmann et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies so far have investigated the impact of L-arginine depletion in neuroinflammatory pathologies [ 26 , 50 ]. Moreover, limited investigation has been conducted on the effects of L-arginine administration on SCI outcome, showing contradictory results [ 29 , 30 , 31 , 32 ]. Tuncer et al and Yüceer and colleagues reported a beneficial effect of L-arginine administration [ 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Esquivel-Aguilar et al found a detrimental impact on functional recovery 8 weeks post-injury after 300 mg/kg L-arginine administration and contusion SCI. Moreover, Savas et al showed an increase of detrimental NO production and NO-mediated cell damage 2 h after ischemia-induced SCI and 100 mg/kg L-arginine administration [ 29 , 31 ]. These conflicting findings might result from differences in the applied L-arginine concentration, the chosen SCI model, and time point for examining the tissue integrity and functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation